Factors Leading to Customer Loyalty in the Domestic Banks in Malaysia – A Perspective from the Social Networking Sites - Kumarashvari, Subramaniam (INTI International University, 2018)
In Malaysia, banks are still struggling to cultivate loyal customers, little agreement among bankers as to what variables contribute to customer loyalty. Numerous empirical studies were conducted to investigate on the factors that lead to customer loyalty but there were no unified solution especially in the Social Networking Sites platform. Therefore, this study intends to investigate the factor leads to customer loyalty by looking into three variables: service value, interactive value and customer experience. Quantitative study was employed with population sampling represented by Facebook community of domestic banks in Malaysia involving a study spanning 6 months (November 2017 – April 2018). It can be concluded that the existence of Social Networking Sites not only augments to social interaction but also extends the experience of having a desirable experience among the consumers. It also offers the banks an opportunity to interact with their target audience resulting in the transfer of marketing messages. Moreover, this study provides an insight to the practitioners on how to provide greater value and promote a more customer centric culture in which service, interactive value and experience can be nurtured from the social media perspective.